Response of City’s Garbage Compost on the Production of Several Varieties of Shallots - Luta, Devi Andriani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
One effort to increase the production of shallots through cultivation techniques is to test several varieties and provide city’s garbage compost. This research was conducted in North Sumatera province in March-April. This research uses the rando draft group (RAK) with2 factors and 3 blocks. The first factor is the varieties (V) and the second factor is the city’s garbage compost (K). the results showed that the most excellent varieties are the Super philip varieties which show the results of wet and dried dry bulbs at most whereas the city’s garbage compost .